PTEN insufficiency modulates ER+ breast cancer cell cycle progression and increases cell growth in vitro and in vivo - Chiang KC; Chen HY; Hsu SY; Pang JHS; Wang SY; Hsu JT; Yeh TS; Chen LW; Kuo SF; Sun CC; Lee JM; Yeh CN; et al. (Dove Medical Press, 2015)
Kun-Chun Chiang,1,4 Huang-Yang Chen,1 Shu-Yuan Hsu,2 Jong-Hwei S Pang,3 Shang-Yu Wang,4 Jun-Te Hsu,4 Ta-Sen Yeh,4 Li-Wei Chen,5 Sheng-Fong Kuo,6 Chi-Chin Sun,7 Jim-Ming Lee,1 Chun-Nan Yeh,4 Horng-Heng Juang21Department of General Surgery, Chang Gung Memorial Hospital, Chang Gung University, Keelung, 2Department of Anatomy, 3Graduate Institute of Clinical Medical Sciences, 4Department of General Surgery, 5Department of Gastroenterology, 6Department of Endocrinology and Metabolism, 7Department of Ophthalmology, Chang Gung Memorial Hospital, Chang Gung University, Keelung, Taiwan, Republic of China Abstract: Phosphatase and tensin homolog (PTEN), a well-known tumor suppressor gene and frequently mutated or lost in breast cancer, possesses the negative regulation function over the PI3K/Akt/mTOR pathway. PTEN insufficiency has been associated with advanced breast cancer and poor prognosis of breast cancer patients. Recently, target therapies aimed at PI3K/Akt/mTOR pathway to treat breast cancer have got popularity. However, the exact effect of PTEN on breast cancer cells is still not well understood. This study demonstrated that PTEN knockdown in MCF-7 cells strengthened the downstream gene expressions, including p-Akt, p-ERK1/2, p-mTOR, p-p70s6k, and p-GSK3ß. PTEN knockdown MCF-7 cells had increased cell growth and Ki-67 expression. Further Western blot demonstrated that p27 was repressed obviously with p21 slightly inhibited and CDK1, 2, 4, 6, cyclin A, and Cdc25C were upregulated in MCF-7 PTEN knockdown cells, leading to the higher growth rate. More importantly, PTEN knockdown MCF-7 cells had higher tumorigenesis and tumor growth in vivo. From our current work, we provided more detailed PTEN-mediated mechanisms to stimulate ER+ breast cancer cell growth. Our result may pave the way for further target therapy development used alone or in combination with other drugs for ER+ breast cancer with PTEN insufficiency.Keywords: PTEN, breast cancer, MCF-7, cell cycle, tumor growth, target therapy